Engineering turbulence modelling and experiments 6 : proce[e]dings of the ERCOFTAC International Symposium on Engineering Turbulence Modelling and Measurements - ETMM6 - Sardinia, Italy, 23-25 May, 2005 /: proce[e]dings of the ERCOFTAC International Symposium on Engineering Turbulence Modelling and Measurements - ETMM6 - Sardinia, Italy, 23-25 May, 2005. (2005) - Unknown
No abstract available